Slit height and blowing pressure as parameters conditioning the function of the clarinet as a quasi-quarter-wave resonator - Bak, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1978)
Using mechanical blowing applied both to a conventional clarinet and to experimental devices with the same reed excitation mechanism, the author has investigated the relationships referred to as "clarinet embouchure". The results confirm John Backus' statement that "Apparently, the intonation characteristics of the clarinet (and, perhaps, the other woodwinds) depend on more than just the geometry of the instrument" (Backus 1964, p. 2014) .